Disability's challenge to theology : genes, eugenics, and the metaphysics of modern medicine - Stahl, Devan (University of Notre Dame Press, 2022)
"Theologians have been debating genetic engineering for decades, but what has been missing from many theological debates is a deep concern for persons with genetic disabilities. In this ambitious and stimulating book, Devan Stahl argues that engagement with metaphysics and a theology of nature is crucial for Christians to evaluate both genetic science and the moral use of genetic technologies, such as human genetic engineering, gene therapy, genetic screenings, preimplantation genetic diagnosis, and gene editing. Using theological notions of creation ex nihilo and natural law alongside insights from disability studies, the book seeks to recast the debate concerning genetic well-being. Following the work of Stanley Hauerwas, Stahl proposes the church as the locus for reimagining disability in a way that will significantly influence the debates concerning genetic therapies. Stahl's project in 'genethics' proceeds with an acute awareness of her own liberal Protestant tradition's early embrace of the eugenics movement in the name of scientific and medical advancement, and it constructively engages the Catholic tradition's metaphysical approach to questions in bioethics to surpass limitations to Protestant thinking on natural law. Christianity has all too frequently been complicit in excluding, degrading, and marginalizing people with disabilities, but the new Christian metaphysics developed here by way of disability perspectives provides normative, theological guidance on the use of genetic technologies today. As Stahl shows in her study, only by heeding the voices of people with disabilities can Christians remain faithful to the call to find Christ in "the least of these" and from there draw close to God. This book will be of interest to scholars in Christian ethics, bioethics, moral theology, and practical theology."--